Practices that can be used to develop innovation ecosystems - Zuiev, Mykhailo; Pushak, Yaroslav (Management and Entrepreneurship: Trends of Development, 2025)
The research examines national innovation ecosystems as strategic economic foundations which create technology progress and boost international competitiveness to fuel national economic expansion. Countries should activate integrated operational methods to encourage partnership activities among government entities and private industry along with academic institutions and civil society organizations because innovation cycles continue to speed up. Research reveals successful innovation ecosystem examples through three essential aspects which include public-private partnership-fostered startup-friendly conditions and cluster association platforms for scientific-industrial synergy and university-business collaborative frameworks for knowledge movement and business innovation. The study provides substantial focus on how Industry 4.0 technologies transform manufacturing operations through automated control and artificial intelligence previously implemented data analytics. Several case studies detailed in the paper showcase successful models of innovation hubs alongside accelerators and regional centers which integrate key stakeholders from Germany, Israel and Ukraine. The approach includes educational efforts together with investment systems and policy-based incentives which support innovation development along with minimizing the early-stage risk. Through research synthesis of international best practice examples the authors provides stepped-up guidance for leaders in business sectors along with academic institutions which need to enhance their innovation capabilities. An analysis confirms the necessity of teamwork between public and private sectors alongside specific funding allocation and planned support structures for building resilient innovation ecosystems which fulfill national requirements and global needs. JEL Classification: O38, O30, L52, H25